Perception of Risk Factors and Determination of Risk Management Strategies According to Agricultural Enterprise Typologies - Zuhal Karakayacı; Zeki Bayramoğlu; Orhan Gündüz; Yusuf Çelik (Turkish Journal of Agriculture: Food Science and Technology)
In this study, it was aimed to determine the risk management strategies and the level of risk perception of the entrepreneurs in agricultural enterprises classified according to production activities. Risk behaviours of entrepreneurs were examined according to the enterprise typologies, and the reference game was used for this purpose. The success of the economic activities of the enterprises was determined by an analysis of the annual operating results. The risk perception was investigated according to the enterprise typology. As a result, it was determined to be perceived as risk factors: drought, fluctuation of input and product prices in the livestock enterprises; drought, precipitation, pests, frost and hail in the mixed plant enterprises; drought, precipitation, frost and hail in the mixed plant and livestock enterprises; pest, diseases, hail, drought and precipitation in the specialized perennial enterprises; storm, capital shortage, loans, price fluctuation, yield fluctuation and fire in the specialized horticulture enterprises; drought, frost, hail, insufficient and unpredictable precipitation in the crop enterprises. The general information on agricultural issues, the implementation of new farming techniques, the diversity in production, the planned debt, the contract production, agricultural protection and the market follow were found out as management strategies for these risk factors.